Message and composition of the Book of Isaiah: an interpretation in the light of Jewish reception history - Laato, Antti (Deuterocanonical and cognate literature studies, 2022)
The series Deuterocanonical and Cognate Literature Studies (DCLS)is concerned principally with research into those books of the Greek Bible (Septuagint) which are not contained in the Hebrew canon, and into intertestamentary and early Jewish literature from the period around the 3rd century BCE to the 2nd century CE. The series was launched in 2007 in collaboration with the "International Society for the Study of Deuterocanonical and Cognate Literature". It provides a logical extension to the Deuterocanonical and Cognate Literature Yearbook, which has been published since 2004.